The Ekphrastic Body: Wayne McGregor's Woolf Works. Issue 2 (4th May 2019) - Fernando, Tanya Jayani
Abstract: In Woolf Works (2015), how does choreographer Wayne McGregor transpose literary modernism into dance? This essay explores how the concept of ekphrasis—the translation of a work of art from one aesthetic medium to another—illuminates McGregor's ballet. The Virginia Woolf novels that McGregor represents in dance contemplate questions of character, beauty, and the sublime. As an analytical framework, ekphrasis helps to examine historical difference inherent in the reinterpretation of artworks. In McGregor's ballet, that difference involves how Woolf's aesthetic categories reappear today.